JDeveloper 11g R2 Jena Adapter Extension - Zdraveski, Vladimir; Trajanov, Dimitar; Efremov, Marjan; Ristoski, Petar (Faculty of Computer Science and Engineering, Ss. Cyril and Methodius University in Skopje, Macedonia, 2012)
Supporting the idea of the semantic web, we developed an intelligent GUI extension for the Oracle JDeveloper 11g R2.ThisGUI extension supports the basic Oracle semantic scenarios (set table space, test query with variables, call prewritten query from file and etc.) from the client side and is also a quite extensive system, thus it is very easy to add an additional functionality. The Jena adapter for Oracle 11g is used to connect to the database engine, placed on the server side. Thus, a complete client side development environment for SPARQL programming is now available and the semantic query management, as a simple concatenation of strings inside the code, seems to becoming just a forgotten nightmare of our semantic web programmer’s life.